2012
DOI: 10.1007/s00595-012-0243-4
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the bleeding of jejunal varices formed at the site of choledochojejunostomy: report of 2 cases and a review of the literature

Abstract: Hemorrhage from jejunal varices formed at the site of Roux-en-Y choledochojejunostomy is rather rare, and no guidelines have so far been established for its treatment. This report presents the cases of 2 patients with jejunal varices formed at the site of choledochojejunostomy that were treated using different methods. An obstruction of the extrahepatic portal vein resulted in massive gastrointestinal bleeding in both cases CASE 1: A 59-year-old male developed jejunal varices at the site of choledochojejunosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…As a result, jejunal bleeding may happen. This event is rare and in literature only case reports or small series have reported it (93)(94)(95)(96), as shown in Table 2. The two main options available are the treatment of the jejunal varices themselves or the decompression of the portal system via a trans-jugular portosystemic shunt; the choice between them generally depends on the clinical status of the patient.…”
Section: Varicesmentioning
confidence: 99%
“…As a result, jejunal bleeding may happen. This event is rare and in literature only case reports or small series have reported it (93)(94)(95)(96), as shown in Table 2. The two main options available are the treatment of the jejunal varices themselves or the decompression of the portal system via a trans-jugular portosystemic shunt; the choice between them generally depends on the clinical status of the patient.…”
Section: Varicesmentioning
confidence: 99%
“…Various treatments have been carried out through the years: portal vein dilatation, portal stenting, bilioenteric reanastomosis, embolization, splenectomy, shunt operation, and endoscopic procedures. [11][12][13][14][17][18][19][20][21][22][23][24][25][26] Neumann et al 13 first reported the treatment using endoscopy. Their case was also a patient with pancreatic cancer whose portal vein was obstructed 1 year after operation.…”
Section: Discussionmentioning
confidence: 99%
“…13 Prachayakul et al used SBE and injected histoacryl into the varicose vein, and although successfully done, thrombosis at the branch of superior mesenteric vein occurred. 14 Saeki et al used DBE and applied Aethoxysklerol (Kaigen Pharma Co., Ltd., Osaka, Japan) for sclerotherapy, but rebleeding occurred 1 week later, forcing them to perform shunt operation. 15 Curcio et al used SBE and endoclips for hemostat, although the clip placement caused varix rupture and cyanoacrylate injection was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…70 The majority of published case reports and small case series of successful management of bleeding jejunal varices in adults are in patients with prior liver transplant, extrahepatic portal venous obstruction, or hepatopancreatobiliary surgery (commonly choledocojejunostomy) which suggests an altered venous collateralization pathway postprocedurally leading to varices at the jejunal anastamosis. 59,[71][72][73][74][75] There are only three cases reported of adults patients with bleeding jejunal varices without portal hypertension or prior surgery, 76 and none in the pediatric literature.…”
Section: Small Bowel and Roux Limb Varicesmentioning
confidence: 99%